Tanggung Jawab Sejarah dan Kebudayaan di Balik Pelarangan Buku di Indonesia - Ayu Rai Wahyuni, Anak Agung (Humanis; Vol 24 No 4 (2020), 2020)
Book prohibition in Indonesia has been going on since the first President of the Republic of Indonesia, Soekarno. This prohibition continued in greater quality and quantity during the reign of the second President of the Republic of Indonesia, Soeharto. In the reform era, when freedom of expression found its space, book prohibition continued. This article examines the historical and cultural responsibility behind book banning. How about the prohibition of books in the Soekarno, Suharto era, and the reform era. What are the pros and cons that occur, as well as what solutions satisfy various parties. The method used is the library method, by reading, inputting data, and studying based on library data.  This article explains that the author of the book must be responsible for the content of his writing. Themes such as the Movement of the PKI are sensitive themes, therefore writers must have historical and cultural awareness. Likewise, the government is expected to be able to review a book, and not to unilaterally freeze or ban it. Bringing a book into the realm of law is supported by the necessary evidence, so that all parties get justice based on the law, history and culture of the nation for the unity of the Republic of Indonesia based on the pillars of development and survival as a nation.